1981
DOI: 10.1128/jcm.13.2.279-282.1981
|View full text |Cite
|
Sign up to set email alerts
|

Rapid method for identification of group B streptococci in neonatal blood cultures

Abstract: A rapid technique used for the identification of Streptococcus agalactiae, Lancefield group B, from the blood cultures of two neonatal infants is reported. The method utilized the Phadebact Streptococcus Test System (Pharmacia Diagnostics, Piscataway, N.J.) and the supernatant from 13-and 14-h blood cultures. Additional studies with simulated neonatal blood cultures revealed that this method was reproducible. Additional studies also revealed that some nonspecific agglutination did occur, which could not be eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For this reason, rapid identification of organisms has been a major area of research in the microbiology laboratory over the past few years. This is evidenced by the numerous studies which have attempted to solve this problem by testing the reliability of different methods of bacterial identification (e.g., latex agglutination, coagglutination, enzyme-linked immunosorbent assay, counterimmunoelectrophoresis) directly on body fluids and blood cultures (1,5,8,11,12).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For this reason, rapid identification of organisms has been a major area of research in the microbiology laboratory over the past few years. This is evidenced by the numerous studies which have attempted to solve this problem by testing the reliability of different methods of bacterial identification (e.g., latex agglutination, coagglutination, enzyme-linked immunosorbent assay, counterimmunoelectrophoresis) directly on body fluids and blood cultures (1,5,8,11,12).…”
Section: Discussionmentioning
confidence: 99%
“…In our study the coagglutination test was chosen because it has been shown to be a very rapid, accurate, and easy test to perform for identifying streptococci (3,7,9). We wanted to expand on previously reported studies (8,11,12) to directly test for streptococcal antigens in blood cultures other than just group B and to include patients of all age groups rather than just infants. We developed a method for direct coagglutination testing for streptococcal groups A, B, C, D, and G by using simulated blood cultures and subsequently used this method to test clinical cultures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations